A new species of the genus Clada Pascoe, 1887 from China (Coleoptera: Ptinidae: Eucradinae) - Huang, Zheng-Zhong; Leng, Shi-Xing; Ge, Si-Qin (Zootaxa, 2026)
Clada (Clada) nyingchiensis Huang sp. nov., a new species belonging to the tribe Hedobiini, is herein described from specimens collected in Mêdog and Zayü counties, located in Nyingchi City of Xizang Autonomous Region (China). Detailed morphological examination of habitus and key diagnostic characters is provided.